Sociological Analysis of Economic Inequalities: Methodological Aspects - Stoyanov, Aleksandar (Research Papers, 2016)
The paper outlines basic elements of the sociological analysis of economic inequalities. The baseline argument of the paper is that economic inequalities are a sociological concept which carries different content in comparison with economic differentiation and heterogeneity of incomes, which in turn are most often perceived as direct proxies of economic inequalities. The theoretical analysis of the concepts of economic differentiation and economic inequality made is focused on their specific interpretation schemes and measurement strategies and methods. The main problematic areas of classic measures of economic differentiation and are outlined including an analysis of most common research findings. The focus on the sociological analysis of economic inequalities (interpreted as status distances between economic roles and resources associated with these roles) includes the principle aspects of this analysis and a comprehensive research program (including concepts and indicators). Some methodological conclusions regarding the interpretations of economic inequalities are made, based on three ISSP surveys (1992, 1999, and 2009). Also based on empirical data some of elements of the outlined research program with regards to Bulgaria are explored: economic differentiation (Gini and extraction ratio), status identification its relationship to subjective social class, etc.
Keywords: Economic differentiation; Economic inequality; Heterogeneity of incomes; Status distances; Social class; Social relations; Subject relations